Improving Basic Movement Learning Outcomes Through a Play Approach to Grade III Students at SDN Manukan Wetan IV/616 - Kharis Prabowo Hadi; Yuli, Sasminta Christina; Nasikin, Nasikin (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
This study aims to determine the increase in basic movement learning outcomes through the play approach in class III students at SD Negeri Manukan Wetan IV/616 in the 2022/2023 academic year. This research is a class action research (CAR) by taking research subjects for class III SD Negeri Manukan Wetan IV/616 for the 2022/2023 academic year, with a total of 37 students. The research was carried out in March 2023 by running for 3 weeks. Data collection techniques in this study used observation and assessment of student learning outcomes. The data analysis technique used in this research is descriptive based on qualitative analysis with percentages. Indicators of the success of the action include increasing basic movement learning outcomes of at least 75% (28 children) of the number of students achieving complete learning outcomes (KKM = 70). After carrying out the research, the results of the first cycle were 35.1% in the "incomplete" category, the second cycle was 56.8% in the "incomplete" category and the third cycle was 78.4% in the "completed" category. With the results of the data analysis, it can be concluded that the basic movement learning outcomes of class III students at SD Negeri Manukan Wetan IV/616 for the 2022/2023 academic year can be improved through a play approach.